2021
DOI: 10.5435/jaaosglobal-d-21-00204
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the COVID-19 Pandemic on the Orthopaedic Surgery Residency Application Process: What Can We Learn?

Abstract: Introduction: The goal of this study was to assess the influence of the coronavirus disease 2019 pandemic on the orthopaedic surgery residency application process in the 2020 to 2021 application cycle. Methods: A survey was administered to the program directors of 152 Accreditation Council for Graduate Medical Education–accredited orthopaedic surgery residency programs. The following questions were assessed: virtual rotations, open houses/meet and greet events, social media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 23 publications
4
28
0
Order By: Relevance
“…Interestingly, spine fellowship programs did not utilize social media as a recruitment tool before or during the pandemic. A study by Wang et al found that compared to the previous year, orthopedic surgery residency programs saw a 355% increase in social media use during the 2020-2021 application cycle [17]. Similar trends were seen for other specialties, including fellowships for other surgical subspecialties [18][19][20].…”
Section: Discussionmentioning
confidence: 86%
“…Interestingly, spine fellowship programs did not utilize social media as a recruitment tool before or during the pandemic. A study by Wang et al found that compared to the previous year, orthopedic surgery residency programs saw a 355% increase in social media use during the 2020-2021 application cycle [17]. Similar trends were seen for other specialties, including fellowships for other surgical subspecialties [18][19][20].…”
Section: Discussionmentioning
confidence: 86%
“…There is also only 1 year of information available for COVID-impacted data. In addition, there is a paucity of information regarding the impact of virtual interviewing on the orthopaedic surgery match process during 2020 to 2021 10 , 11 , 18 , 19 . Even if such data existed, the extreme variability in the structure of each virtual rotation would require further analysis based on offerings of the rotation.…”
Section: Discussionmentioning
confidence: 99%
“…Applicants reported that social media content posted by residencies influenced their interest in programs 9 . Residency programs found social media to be more helpful than previous years and placed importance on virtual rotations during resident recruitment 11 . The authors believe that a lack of away rotations would lead to an observable difference in both geographic and affiliated program matching during the COVID-impacted match cycle because these virtual engagement opportunities were not universally adopted or sufficient to prevent programs and applicants from matching to programs they were most familiar with.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies across medical specialties have identified online presence both in Web site and social media as a determining factor in fellowship selection among new physicians. [2][3][4][5][6][7][8][9][10][11][12][13] Fellowship program Web sites (FPWs) have been assessed across medical specialties for content relevant to applicants. 14,15 As part of this assessment, authors established criteria to describe FPW content that may be utilized as a comparative scoring method.…”
mentioning
confidence: 99%